PENGARUH PENAMBAHAN LARUTAN SURFAKTAN PADA LARUTAN POLIMER TERHADAP TEGANGAN ANTARMUKA DAN VISKOSITAS - Nindya Az-zahra; Lestari Lestari; Havidh Pramadika (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
This laboratory research uses surfactant X concentrations 0.05%, 0.1%, 0.3%, 0.5%, and 1%; with polymer P40 concentrations 500 ppm, 750 ppm, 1000 ppm, 1250 ppm, 1500 ppm, and 2000 ppm. The purpose of this study was to determine the addition of surfactant to polymer on viscosity and interfacial tension values.The lowest (CMC) interfacial tension value resulted in concentration 0.3% which is 8.08-E03 dyne/cm. With the addition of 0.3% surfactant to polymer solution (500 ppm, 750 ppm, 1000 ppm, 1250 ppm, 1500 ppm, and 2000 ppm) resulted in a decrease on viscosity value from 4.13 cp, 5.43 cp, 7.26 cp, 9.44 cp, 12.67 cp, and 20.68 cp to 3.52 cp, 5.1 cp, 6.82 cp, 9.23 cp, 11.35 cp, and 19.28 cp, also an increase on interfacial tension value from 8.08 dyne/cm to between 1-E02 dyne/cm.